Zakres sądowej kontroli decyzji podjętych w indywidualnych sprawach studentów i doktorantów - Daniel, Paweł (Wydawnictwo Naukowe UAM, 2015)
Under Art. 207 para. 1 of the Law on Higher Education, the decisions taken in individual cases concerning students and doctoral students fall under the provisions of the Act of 14 June 1960: “The Code of Administrative Procedure and the provisions of the making a complaint to the administrative court”. An analysis of the judgments of administrative courts shows that the judicial review of decisions concerning the above matters remains an open question. Hence the purpose of this study was to determine which cases relating to students and doctoral students are subject to judicial review. The depth, or detail, of the jurisdiction of administrative courts in those cases has also been examined. The undertaken considerations led to the conclusion that the scope of a judicial review of decisions taken in individual cases concerning students and doctoral students is patchy. The case law of administrative courts shows that exposure to the jurisdiction of the court is not limited to the sphere of relations in which the taken decision has legal effects; it must be determined whether a particular decision is taken on the basis of the provisions of the Act. In the context of a judicial review, the court is entitled to review the legality of general internal acts as long as they are the basis of the settlement in an individual case. At the same time, however, the court cannot control the acts of individual internal acts, even if they often constitute the basis for issuing a decision. In other words, an administrative court is not entitled to control the decisions taken on the basis of internal company acts which do not have any effect on the external environment and do not have a direct impact on the legal relation between a student and a university. A complaint on the inactivity of an administrative body of an establishment of higher education will be acceptable as long as such body has remained idle and fails to deliver an act or take an action pursuant to the existing legislation.
The scope of judicial review of decisions made in individual cases concerning undergraduate, graduate and doctoral students
Keywords: university; individual cases of students and doctoral students; judicial review